2015
DOI: 10.1063/1.4931972
|View full text |Cite
|
Sign up to set email alerts
|

High reactivity of nanosized niobium oxide cluster cations in methane activation: A comparison with vanadium oxides

Abstract: The reactions between methane and niobium oxide cluster cations were studied and compared to those employing vanadium oxides. Hydrogen atom abstraction (HAA) reactions were identified over stoichiometric (Nb2O5)N(+) clusters for N as large as 14 with a time-of-flight mass spectrometer. The reactivity of (Nb2O5)N(+) clusters decreases as the N increases, and it is higher than that of (V 2O5)N(+) for N ≥ 4. Theoretical studies were conducted on (Nb2O5)N(+) (N = 2-6) by density functional calculations. HAA reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…As observed in the comparison of [MCH 2 ] + and [MO 2 ] + (M = V, Nb, Ta), , the increased reactivity of tantalum-containing compounds is generally attributed to relativistic effects that enable the formation of very strong Ta–C bonds. Instead of dehydrogenation and concomitant H 2 evolution, a direct hydrogen-atom transfer (HAT) mechanism prevails for many metal oxide systems that contain terminal , (and less for bridging) oxygen atoms with localized spin density, for example, stoichiometric vanadium and niobium oxide clusters . In these systems, the local charge influences reaction barriers .…”
Section: Introductionmentioning
confidence: 99%
“…As observed in the comparison of [MCH 2 ] + and [MO 2 ] + (M = V, Nb, Ta), , the increased reactivity of tantalum-containing compounds is generally attributed to relativistic effects that enable the formation of very strong Ta–C bonds. Instead of dehydrogenation and concomitant H 2 evolution, a direct hydrogen-atom transfer (HAT) mechanism prevails for many metal oxide systems that contain terminal , (and less for bridging) oxygen atoms with localized spin density, for example, stoichiometric vanadium and niobium oxide clusters . In these systems, the local charge influences reaction barriers .…”
Section: Introductionmentioning
confidence: 99%
“…The Stuttgart/Dresden effective core potential (SDD) was used for Nb and V atoms, where 10 electrons of V and 28 electrons of Nb were treated as the core, whereas for O, the 6-311G(d) basis set was used. For even n clusters, previously reported structures 10,11,15,16,24 + and V 3 O 7 + from their ion mobility measurements and those calculated by Asmis et al for infrared multiple photon dissociation spectroscopy were referenced. 13,16,25 The most stable geometries had singlet spin multiplicity, except for V 3 O 6 + in the triplet state.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…15 He et al found that niobium oxide and vanadium oxide clusters could dehydrogenate methane and determined the most stable structures of (Nb 2 O 5 ) n + clusters. 10 They showed that niobium oxide clusters had higher reactivity than vanadium oxide clusters and that larger niobium oxide clusters are less reactive. Misaizu et al determined the structure of vanadium oxide clusters by ion mobility mass spectrometry.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations were carried out to determine the stable structures of Nb n V m O k + clusters ( n + m = 2, 3, and 4) using the Gaussian09 program, and to investigate the binding energies of the clusters . Becke’s three-parameter hybrid density functional with the Lee–Yang–Parr correlation functional (B3LYP) was used for all the calculations. , The Stuttgart/Dresden effective core potential (SDD) was used for the Nb and V atoms, where 10 electrons of V and 28 electrons of Nb were treated as the core, whereas for O the 6-311+G­(d) basis set was used. , For n + m = 2 clusters, previously reported structures of Nb 2 O 5 + were referenced. ,, The initial geometries of the clusters of interest were set by adding one O atom to and removing one O atom from possible sites. The most stable geometries had doublet spin multiplicity.…”
Section: Computational Sectionmentioning
confidence: 99%